2017
DOI: 10.1371/journal.pone.0188301
|View full text |Cite
|
Sign up to set email alerts
|

Morphological correlation between caloric tests and vestibular hydrops in Ménière's disease using intravenous Gd enhanced inner ear MRI

Abstract: The purpose of this study was to prove the hypothesis that caloric response in Ménière's disease (MD) is reduced by hydropic expansion of the vestibular labyrinth, not by vestibular hypofunction, by evaluating the correlation morphologically using an intravenous Gadolinium (IV-Gd) inner ear MRI. In study I, the prevalence of abnormal video Head Impulse Test (vHIT) results among the patients with definite unilateral MD (n = 24) and vestibular neuritis (VN) (n = 22) were investigated. All patients showed abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…In our study also caloric tests showed better sensitivity compared to VHIT especially in patients with chronic complaints. 14 Our results suggest that unilateral vestibular hypo activity is the cornerstone in the diagnosis of peripheral vestibular lesions as stated in many other researches. However, it has to be evaluated with other data in order to find out the exact location of the lesion.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study also caloric tests showed better sensitivity compared to VHIT especially in patients with chronic complaints. 14 Our results suggest that unilateral vestibular hypo activity is the cornerstone in the diagnosis of peripheral vestibular lesions as stated in many other researches. However, it has to be evaluated with other data in order to find out the exact location of the lesion.…”
Section: Discussionsupporting
confidence: 77%
“…Also, the extent of hydrops correlates with the extent of caloric weakness with normal VHIT tests. 7,12,14 Choi et al of 2007 also pointed out the same discrepency. In our study also caloric tests showed better sensitivity compared to VHIT especially in patients with chronic complaints.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, hydrops of endolymphatic duct could be the cause of caloric deficit without compromising the vestibulo-ocular reflex (VOR) response in vHIT. In the author’s other paper, we found out the morphological correlation between caloric tests and vestibular hydrops in MD patients with normal vHIT 30 . The patients with abnormal vHIT were excluded.…”
Section: Discussionmentioning
confidence: 79%
“…The distended membranous duct of the horizontal SCC has been suggested to permit convective recirculation within the duct, leading to a diminished thermally-induced pressure gradient across the cupula and thus to less deflection of the cupula and hair cells and less caloric nystagmus. This assumption is supported by the observation that, in MD patients with normal vHIT results, the reduced caloric response was correlated with the severity of vestibular hydrops (as demonstrated by intravenous gadolinium-enhanced MRI of the inner-ear) (21). Second, the dual frequency hypothesis proposes that a differential activation of vestibular hair cells by stimuli with different frequencies might be responsible for the dissociation.…”
Section: Discussionmentioning
confidence: 88%